Single-crystal ZrCo nanoparticle for advanced hydrogen and H-isotope storage - Li, Zhenyang; Liu, Shiyuan; Pu, Yanhui; Huang, Gang; Yuan, Yingbo; Zhu, Ruiqi; Li, Xufeng; Chen, Chunyan; Deng, Gao; Zou, Haihan; Yi, Peng; Fang, Ming; et al. (Nature communications, 2023)
Hydrogen-isotope storage materials are essential for the controlled nuclear fusion. However, the currently used smelting-ZrCo alloy suffers from rapid degradation of performance due to severe disproportionation. Here, we reveal a defect-derived disproportionation mechanism and report a nano-single-crystal strategy to solve ZrCo’s problems. Single-crystal nano-ZrCo is synthesized by a wet-chemistry method and exhibits excellent comprehensive hydrogen-isotope storage performances, including ultrafast uptake/release kinetics, high anti-disproportionation ability, and stable cycling, far superior to conventional smelting-ZrCo. Especially, a further incorporation of Ti into nano-ZrCo can almost suppress the disproportionation reaction. Moreover, a mathematical relationship between dehydrogenation temperature and ZrCo particle size is established. Additionally, a microwave method capable of nondestructively detecting the hydrogen storage state of ZrCo is developed. The proposed disproportionation mechanism and anti-disproportionation strategy will be instructive for other materials with similar problems. ZrCo, a promising hydrogen isotope storage material, has poor cyclic storage capacity. Here author reveal a defect-derived disproportionation mechanism and report a nano-single-crystal strategy to comprehensively improve performances.